Day 3 Thu, March 22, 2018 2018
DOI: 10.4043/28534-ms
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Detection Ahead of the Bit – A Sensitivity Study of Extra Deep Azimuthal Resistivity

Abstract: The opportunity to detect boundaries ahead of the bit has long been a desire within the oil and gas industry as it would allow precise geo-stopping prior to entering unwanted formations and/or fluids. There are solutions already available such as the use of seismic applications. However these are for use on a different resolution scale, the accuracy needed for geo-stopping within meters of a formation boundary is lacking. Extra Deep Azimuthal Resistivity (EDAR) has been widely used for geosteeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The Schumann resonance has been observed at frequencies as 7.5 Hz, 14.5 and 20.5 Hz (Larsen et al., 2018). It could also be used to verify the performance of the proposed method.…”
Section: Numerical Examples and Discussionmentioning
confidence: 99%
“…The Schumann resonance has been observed at frequencies as 7.5 Hz, 14.5 and 20.5 Hz (Larsen et al., 2018). It could also be used to verify the performance of the proposed method.…”
Section: Numerical Examples and Discussionmentioning
confidence: 99%
“…The most useful and used measurements for geosteering are electromagnetic (EM) measurements, which combine reliability with deep sensitivity (depth of investigation). The current generation of extradeep EM tools (also referred to as ultra-deep EM) can detect remote boundaries up to 60 m away from measurement location (Wu et al, 2019), and recent publications have also revealed sensitivity ahead of bit (Larsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Third, a forward deep neural network (FDNN) converts the 1D inputs to synthetic EM logs: a full suite of extra-deep EM log traces transmitted in real-time during drilling(Alyaev et al, 2021). The extra-deep EM logs include 22 measurements with a sensitivity of up to 20 meters from the tool(Larsen et al 2018). For one realization, the entire modelling sequence takes around 0.12s to model nine logging positions along the well path on a 3.3 GHz (4.5 GHz turbo) core.…”
mentioning
confidence: 99%